Avaliação da compatibilidade entre competências requeridas e competências desenvolvidas: o caso da Universidade Federal de Santa Maria - Costa, Fabricio da (2020)
The present study aimed to propose a schedule of courses, to fill the skills gaps found, to technical-administrative servants in education (TAES) of the Federal University and Santa Maria (UFSM). The theoretical framework guiding this study covered the following topics: (i) public administration and people management; (ii) main regulations for people management in the federal administration; (iii) competency management; (iv) management by competencies in the public sector; (v) competency management and training needs and (vi) competencies in federal educational institutions. Regarding the method, the study was characterized as a qualitative research, making use of different sources of evidence such as: documentary research, registration in files, direct observation and participant observation. The main results show that UFSM started the studies for the implementation of the competency management model in 2015, through a work group formed by employees working in the University's Dean of Personnel Management. In 2017, a commission was formally constituted through a specific ordinance, to act more effectively in the implementation of the model in the institution. The work started by mapping the competencies of the servers, which were classified and divided into four phases. The first three phases, already completed, correspond to the mapping of organizational, common and managerial skills. The fourth phase, referring to the mapping of specific competencies, which are those necessary for each of the UFSM units, is still being carried out by the current commission. The results also revealed that the implementation of the competency management model at UFSM is among the strategic objectives foreseen in its current Institutional Development Plan - PDI (2016-2026), which brings the intention to develop managerial, technical and leadership skills necessary to maintain a level of excellence. Still, the results showed that the compatibility between the skills required by UFSM and the skills developed through the training courses offered to TAES servers, based on the years 2018 and 2019, proved not to be fully met, as from the analysis of the 115 courses offered in these two years, only 07 of them worked on the development of managerial and / or leadership skills. Finally, it was presented the proposal to carry out a course schedule to be promoted by the Center for Education and Development (NED) of the Pro-Rectory for People Management at UFSM, aiming to fill the identified skills gaps.